Computer accounting with Sage 50 complete accounting 2013 [formerly Peachtree] - Yacht, Carol
Carol Yacht's Peachtree textbook is the market leader because her pedagogy is unmatchedshe incorporates real-world businesses; step-by step-directions; numerous screen illustrations; challenging exercises and projects; and a website with additional resources. In Computer Accounting with Sage 50 Complete Accounting 2013, 17th Edition, you learn about the relationship between Sage 50 software and fundamental accounting principles, procedures, and business processes. The primary goal is for the student to have a working familiarity with the software after completing the course with this text